BLOW-UPOF SOLUTIONS OF A NONLINEAR KIRCHHOFF'S EQUATION WITH DAMPING TERM - Quispe Méndez, Teófanes (2004)
We study the blow-up in finite time of the local solutions to the mixed problem for a type of nonlinear Kirchhoff's equation with damping term.